Analysis of lowland rice peat land in Mampai Village, Kapuas Murung District, Kapuas-Kalimantan Central District - Sunaryati, Revi; Wahib Muhaimin, Abdul (Anjoro: International Journal of Agriculture and Business, 2022)
Central Kalimantan is a province where the agricultural sector is still the basis for economic cohesion. Mampai Village, Kapuas Murung District, Kapuas District, Central Kalimantan is a peatland rice field. Peat soil is wet soil and stores a lot of acid, so it is not easy to use or to grow crops. The purpose of this study was to determine the general description of lowland rice farming held in Mampai Village and to determine the amount of lowland rice income and its contribution to the total income of lowland rice RTP in Mampai Village, Kapuas Murung District, Kapuas District, Central Kalimantan Province. The results of descriptive analysis of the general description of farming in rice fields in Mampai Village, Kapuas Murung District, Kapuas Regency have implemented farming intensification technology well where farmers have implemented a cropping pattern 2 times a year, namely MT I and MT II with an average cultivated area of 2.40 ha. pe MT. The results of the analysis of lowland rice income obtained forone year by farmers amounted to Rp. 36,355,109 and contributes 74.93%, this shows that the role of lowland rice farming for farmers in Mampai Village is very important, thus it can be said that rice field rice farmer households in Mampai Village, Kapuas Murung District, Kapuas District, Central Kalimantan, are categorized as not poor.